OPTIMIZATION OF HIV-1 PROTEASE PURIFICATION USING IMPACT (INTEIN MEDIATED PURIFICATION WITH AN AFFINITY CHITIN-BINDING TAG) FOR DEVELOPMENT OF ANTI-HIV DRUG SCREENING METHOD - Nur'Azmi, Akifah
Human Immunodeficiency Virus (HIV) is one of the deadliest and most dangerous pathogen by hijacking our immune system. Currently HIV can be controlled by using antiretroviral therapy (ART), a drug that inhibits viral replication process. One group of ART drugs with a high genetic barrier is HIV protease inhibitor. However, the availability of ART is very limited, especially in developing countries like Indonesia. Thus, it is necessary to develop new anti-HIV drugs by utilizing Indonesian resources. One method of developing HIV drugs is screening of candidate compounds which can deactivate HIV proteases by preventing invitron protease dimerization. However, the method of screening the drug requires a large number of pure HIV proteases. Affinity purification is a widely used method for obtaining protein of high purity. Many of these methods have the drawbacks of either leaving the recombinant tag attached to the protein or requiring the addition of protease which then must be removed by further chromatographic steps. The use of these proteases was known to be time and cost inefficient. In this study, HIV-1 protease purification was carried out using IMPACT method, by using this purification system, the target protein was fused to protein markers, intein and CBD (Chitin-binding Domain). Intein has self-cleavage activity when induced using thiol. Therefore, the purification system allows protein purification by only one chromatography step, without the use of proteases. The purpose of this study was to purify HIV-1 protease using IMPACT method at its optimum conditions. The method in the study began with the construction of the plasmid pTXB1 inserted by the HIV-1 protease gene, followed by the transformation of the plasmid into Escherichia coli BL21 (DE3), the results of transformation were then confirmed by PCR and sequencing. The protein was then expressed from the transformant culture and solubilized. Then, protein purification optimized by: varying DTT and ?-mercaptoethanol as cleavage compound in the cleavage buffer (trisbasa pH 8.5); increasing DTT concentration from 50 mM to 60 mM; increase pH of cleavage buffer from 8.5 to 9.2; varying the incubation temperature of the resin column, at 4 ° C and room temperature; Protein analysis was performed using SDS PAGE method. . In previous studies, plasmid confirmed the presence of a protease gene measuring around 300 bp. From the results of protein analysis, HIV-1 proteases have a size of about 35 kDa. Based on this study, it is known that the cleavage activity of protease from the tag protein (intein-CBD) was successfully observed, which occurred when the column was induced using cleavage buffer pH 9.2, with a thiol compound DTT (50 mM). The optimum column incubation temperature (after thiol induction) is 4 ° C. Even so, protease band was not observed in well elution results from SDS-PAGE. Hence, it is assumed that the HIV-1 protease has been successfully purified in this research, using IMPACT method. However, to be visualized on acrylamide gel, HIV-1 protease concentration still needs to be increased. Crosslink dimerization experiment of the purified protease was prepared to confirm that it did not undergo any significant change in protein folding that would affect its dimerization capability. Following the hardship in collecting pure HIV-1 protease throughout this research, crosslink dimerization experiment was done using the fused protein (HIV-1 protease + intein + CBD) instead of purified protease HIV-1, to observe possible dimerization in HIV-1 protease that were still fused with intein and CBD. The experiment was carried out at a concentration ratio of fusion protein: crosslinker agent (BS3) 1:20, incubated in 37?C for 4 hours. Based on these experiments, it was found that fusion protein dimerization using the crosslink dimerization method was not successful.